Low-Latency f0 Estimation for the Finger Plucked Electric Bass Guitar Using the Absolute Difference Function - Fonseca, Christhian; Tavares, Tiago (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
Audio-to-MIDI conversion can be used to allow digital musical control by means of an analog instrument. Audio-to-MIDI converters rely on fundamental frequency estimators that are frequently restricted to a minimum delay of two fundamental periods. This delay is perceptible for the case of bass notes. In this paper, we propose a lowlatency fundamental frequency estimation method that relies on specific characteristics of the electric bass guitar. By means of physical modelling and signal acquisition, we show that the assumptions of the method relies on generalize throughout electric basses. We evaluate our method in a dataset with musical notes played by diverse bassists. Results show that our method outperforms the Yin method in low-latency settings, which indicates its suitability for low-latency audio-to-MIDI conversion of the electric bass sound.